Plasma Markers of Neurologic Injury and Inflammation in People With Self-Reported Neurologic Postacute Sequelae of SARS-CoV-2 Infection. Issue 5 (14th September 2022) - Peluso, Michael J.; Sans, Hannah M.; Forman, Carrie A.; Nylander, Alyssa N.; Ho, Hsi-en; Lu, Scott; Goldberg, Sarah A.; Hoh, Rebecca; Tai, Viva; Munter, Sadie E.; Chenna, Ahmed; Yee, Brandon C.; et al.
Abstract : Background and Objectives: The biologic mechanisms underlying neurologic postacute sequelae of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (PASC) are incompletely understood. Methods: We measured markers of neurologic injury (glial fibrillary acidic protein [GFAP], neurofilament light chain [NfL]) and soluble markers of inflammation among a cohort of people with prior confirmed SARS-CoV-2 infection at early and late recovery after the initial illness (defined as less than and greater than 90 days, respectively). The primary clinical outcome was the presence of self-reported CNS PASC symptoms during the late recovery time point. We compared fold changes in marker values between those with and without CNS PASC symptoms using linear mixed-effects models and examined relationships between neurologic and immunologic markers using rank linear correlations. Results: Of 121 individuals, 52 reported CNS PASC symptoms. During early recovery, those who went on to report CNS PASC symptoms had elevations in GFAP (1.3-fold higher mean ratio, 95% CI 1.04–1.63, p = 0.02), but not NfL (1.06-fold higher mean ratio, 95% CI 0.89–1.26, p = 0.54). During late recovery, neither GFAP nor NfL levels were elevated among those with CNS PASC symptoms. Although absolute levels of NfL did not differ, those who reported CNS PASC symptoms demonstrated a stronger downward trend over time in comparison with those who did not report CNS PASC symptoms ( p = 0.041). Those who went on to report CNS PASC also exhibited elevations in interleukin 6 (48% higher during early recovery and 38% higher during late recovery), monocyte chemoattractant protein 1 (19% higher during early recovery), and tumor necrosis factor α (19% higher during early recovery and 13% higher during late recovery). GFAP and NfL correlated with levels of several immune activation markers during early recovery; these correlations were attenuated during late recovery. Discussion: Self-reported neurologic symptoms present approximately 4 months after SARS-CoV-2 infection are associated with elevations in markers of neurologic injury and inflammation at earlier time points. Some inflammatory pathways seem to be involved months after acute infection. Additional work will be needed to better characterize these processes and to identify interventions to prevent or treat this condition.